Perceived discomfort for typical helicopter vertical sine vibrations for seated participants - Delcor, Laurianne; Parizet, Etienne; Ganivet-Ouzeneau, Julie; Caillet, Julien (Journal of Low Frequency Noise, Vibration and Active Control, 2021)
Vibrations contribute to helicopter’s ride comfort. This study aimed to determine the relationship between main rotor vertical excitations and discomfort. Fifty-three participants, seated on a helicopter seat fixed to a vibration test bench, evaluated the discomfort of vertical sinusoidal vibrations using a magnitude estimation procedure. Stimuli had a frequency between 15 and 30 Hz and a level between 0.32 and 3.16 m/s2. The average discomfort was shown related to vibration velocity using Steven’s power law, without any frequency dependence. The exponent depended on velocity and was 1.18 for higher velocities (approx. above 0.008 m/s) and 0.65 for velocities below that limit.